Metal-loaded super-hydrophobic air electrode, preparation method and chlorine production application

By designing a metal-loaded superhydrophobic air electrode, the cathode utilizes atmospheric oxygen and the anode utilizes dissolved oxygen to generate active chlorine, solving the problems of high energy consumption and numerous byproducts in existing electrochemical disinfection technologies, and achieving low energy consumption, long lifespan, and safe electrochemical chlorine production.

CN121020744APending Publication Date: 2025-11-28NINGBO UNIV

Patent Information

Application Number
CN202511556145.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-29
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing electrochemical disinfection technologies are energy-intensive, have numerous side reactions, and are prone to producing disinfection byproducts. Traditional gas diffusion electrodes require external aeration equipment, resulting in high system energy consumption and easy electrode wear, making it difficult to meet long-term stable water treatment needs.

Method used

It employs a metal-loaded superhydrophobic air electrode with a symmetrical electrode configuration. Both the anode and cathode use metal-loaded superhydrophobic air electrodes. The cathode utilizes atmospheric oxygen, and the anode utilizes dissolved oxygen to generate active chlorine, avoiding external aeration. The operating potential window is lower than the oxygen evolution reaction potential, suppressing side reactions.

Benefits of technology

It significantly reduces system energy consumption, inhibits the generation of disinfection byproducts, improves electrode life and chlorine production efficiency, reduces operating costs, and enhances operational safety and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121020744A_ABST
    Figure CN121020744A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of air electrode preparation, in particular to a metal-loaded super-hydrophobic air electrode, a preparation method and chlorine production application, the air electrode comprises a high-hydrophobicity gas diffusion layer obtained through polytetrafluoroethylene modification, and the metal-loaded super-hydrophobic air electrode is prepared through a corona etching and electrochemical in-situ deposition technology. A uniform and highly-dispersed metal catalyst layer directly grows on the surface of the polytetrafluoroethylene substrate, so that the gas diffusion electrode with excellent mass transfer performance and an efficient catalytic function is obtained; the prepared electrode is used for carrying out electrochemical catalysis on a water body containing chloride ions by adopting a cyclic voltammetry method, and active chlorine can be efficiently generated in situ; the prepared metal-loaded super-hydrophobic air electrode has the advantages of being low in oxygen mass transfer resistance, high in catalyst utilization rate, free of generation of by-products, capable of efficiently generating active chlorine and the like, and has wide application potential in actual water environment disinfection.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of air electrode preparation, and particularly relates to a metal-loaded super-hydrophobic air electrode, a preparation method and a chlorine production application. BACKGROUND

[0002] In the field of drinking water safety guarantee, the traditional chlorine disinfection process inactivates pathogenic microorganisms such as bacteria and viruses in water bodies through long-term chemical oxidation, effectively blocking the spread of water-borne infectious diseases; but its defects are also significant, when treating water bodies containing organic matter, the process is easy to generate disinfection by-products with carcinogenic risk, which poses potential harm to the environment and human health, at the same time, chlorine disinfection needs to transport and store hazardous chemicals on site, which not only reduces the safety of operation, but also increases the economic cost and land area, which is difficult to adapt to the efficient and safe needs of modern water treatment; in order to solve the pain points of traditional process, electrochemical disinfection technology gradually enters the field of vision, its advantages are that it can generate disinfectant on site as needed from water source, without the need for additional electrolyte salt, and it has the characteristics of high automation and controllable disinfection by-products, however, the existing electrochemical disinfection technology still faces multiple bottlenecks, the chlorine evolution reaction needs a higher anode potential, which directly leads to a significant increase in system energy consumption, and the more likely water oxidation reaction will form a fierce competition with the chlorine evolution reaction, further increasing the energy consumption of active chlorine generation; at the same time, in the environment of high anode potential, natural organic matter, urea, amino acid and other substances in the water body will be directly oxidized by the anode, and then carbon-based and nitrogen-based disinfection by-products will be generated, which will increase the risk of secondary pollution; although the industry currently uses size-stable anodes or boron-doped diamond electrodes to improve the above problems, such electrodes not only have high manufacturing costs, but also generate strong free radicals that indiscriminately oxidize organic matter in water, which in turn leads to the generation of more disinfection by-products; in addition, the electrode configuration and operation mode of the existing electrochemical disinfection system also need to be optimized, the traditional gas diffusion electrode needs to rely on external aeration equipment to ensure oxygen supply, which further increases the system energy consumption and complexity, and the electrode is prone to active decay and uneven wear during long-term operation, leading to a decrease in chlorine production efficiency and a short service life, which is difficult to meet the long-term stable water treatment needs.

[0003] Therefore, it is of great significance to develop an electrode that can operate in a low potential window, does not need external aeration, can inhibit the generation of disinfection by-products, and has a long service life, to promote the industrial application of electrochemical disinfection technology and improve the safety and economy of drinking water treatment, which has become a technical problem to be solved in the field of electro-catalytic water treatment. SUMMARY

[0004] The present application aims at the problems of high energy consumption, many side reactions and easy generation of disinfection by-products in existing electrochemical disinfection technology, and proposes a metal-loaded super-hydrophobic air electrode, a preparation method and chlorine production application. A symmetric electrode configuration is adopted, and the cathode and anode both use the metal-loaded super-hydrophobic air electrode prepared by the present application, and a cyclic voltammetry method is used to synchronously drive the cathode and anode to operate at a low potential window. In this process, one electrode is used as a floating air-breathing cathode to directly use the oxygen in the air, and the other electrode is used as an immersed air-diffusion anode to use the oxygen and dissolved oxygen in the water to participate in the reaction, so that the external aeration equipment required by the traditional gas diffusion electrode is saved, and the system energy consumption is significantly reduced. When the cathode voltage acts on the floating side electrode, the reduction current promotes the step-by-step reduction of oxygen to generate hydrogen peroxide, and further generates hydroxyl radicals under the catalysis of the metal material. On the other side electrode under the action of the anode voltage, the chlorine ions react with the in-situ generated hydroxyl radicals to generate hypochlorite and other active chlorine species. The potential window is much lower than the oxygen evolution potential, which fundamentally inhibits the high-potential side reactions such as anode oxygen evolution, and effectively prevents the generation of chlorine-containing disinfection by-products.

[0005] To specifically illustrate the preparation method of the present application, the construction process of the metal catalyst super-hydrophobic air cathode is shown. This selection is only an example for clearly illustrating the process and effect of the present application, and is not a limitation of the claims. Any equivalent material replacement based on the core idea of the present application should be considered as falling within the protection scope of the present application.

[0006] The first aspect of the present application provides a metal-loaded super-hydrophobic air electrode, which comprises: a porous substrate; a polytetrafluoroethylene modified layer formed on the porous substrate by an impregnation sintering method, which makes the substrate super-hydrophobic; and a metal catalyst layer directly grown on the surface of the polytetrafluoroethylene modified layer.

[0007] Preferably, the porous substrate is an IF8@zirconia porous substrate.

[0008] Preferably, the preparation method of the IF8@zirconia porous substrate comprises: S1. Preparing a porous zirconia with a three-dimensional through network structure by a foam template method combined with a sintering process; S2. Dissolving zirconium salt, organic ligand and adjusting agent in an organic solvent to prepare an IF8 crystal dispersion liquid by a solvothermal reaction; S3. Immersing the porous zirconia carrier in the IF8 crystal dispersion liquid, and using vacuum-assisted impregnation and a secondary solvothermal method to make the IF8 crystals grow in situ on the pores and surface of the porous zirconia to form an IF8@zirconia composite structure; S4, taking out the loaded composite material, cleaning with an organic solvent and drying, and then annealing and activating under an inert atmosphere to obtain the IF8@zirconia porous substrate.

[0009] Preferably, the metal catalyst is selected from any one of platinum, palladium, gold, iridium, ruthenium, or an alloy or composite nanomaterial composed of a noble metal and one or more non-noble metals such as iron, cobalt, nickel, copper, and manganese.

[0010] The second aspect of the present application provides a preparation method of a metal-loaded super-hydrophobic air electrode, comprising the following steps: (1) The pre-cut IF8@zirconia porous substrate of a specific size is sequentially placed in an ethanol solution and deionized water, and ultrasonic treatment is performed in an ultrasonic cleaning machine for 25 min. After cleaning, the substrate is dried in a vacuum drying oven at 70°C for 6 h, cooled to 25°C, and taken out to obtain a pretreated substrate.

[0011] It can be understood that, in the present application, ethanol is used as a polar organic solvent to efficiently dissolve organic contaminants remaining on the surface and in the pores of the substrate; deionized water further washes away the residual ethanol and water-soluble inorganic impurities, and the cavitation effect generated by the high-frequency vibration of ultrasonic cleaning forms tiny bubbles in the liquid, which release strong impact force when they burst, allowing stubborn impurities adhering to the pore walls to be completely stripped and dispersed in the cleaning solution, thereby achieving omnidirectional cleaning of the surface and internal pores of the substrate. The subsequent step of vacuum drying at 70°C has dual advantages: on the one hand, the vacuum environment reduces the boiling points of water and ethanol, allowing the residual solvents to rapidly vaporize at a lower temperature, thereby avoiding high-temperature decomposition of the IF8 active component or phase transition of the crystal structure of the zirconia substrate, and effectively protecting the original physical and chemical properties of the substrate; on the other hand, slowly cooling to 25°C can reduce internal stress caused by sudden temperature changes, preventing cracks in the porous structure due to thermal expansion and contraction, and ensuring the integrity of the substrate.

[0012] The pretreated substrate obtained finally not only has high cleanliness and thorough drying, but more importantly, the porous structure characteristics of the IF8@zirconia are completely preserved. Figure 1 As shown in FIG. 1, the porous structure significantly reduces the mass transfer resistance of oxygen inside the electrode through the network of interconnected channels, providing an efficient gas transport channel for subsequent catalytic reactions; at the same time, the clean surface and pore walls can eliminate the coverage or poisoning of impurities on the active sites of IF8, ensuring uniform attachment of functional materials in the subsequent loading process and effective participation of active components in the reaction process, thereby improving the accuracy, repeatability of experimental results, and stability of the catalytic performance of the final product.

[0013] (2) The pretreated substrate is completely immersed in a polytetrafluoroethylene dispersion with a solid content of 10%-30% for 5-10 min, then taken out and hung vertically for 1-3 min to drain. After drying, it is sintered in a muffle furnace with a heating rate of 5-10℃ / min, heated to 300-380℃, and held for 20-40 min to obtain a polytetrafluoroethylene modified substrate.

[0014] It is understood that in this embodiment, the pretreated substrate is completely immersed in a polytetrafluoroethylene (PTFE) dispersion with a solid content of 10%-30%. The wettability of the liquid allows the PTFE particles to fully adhere to the substrate surface and gaps. Immersion for 5-10 minutes ensures uniform penetration of the dispersion into the three-dimensional porous structure. After removal, the substrate is hung vertically to drain for 1-3 minutes, and excess dispersion is removed by gravity to prevent uneven coating caused by localized PTFE accumulation. Drying removes the solvent from the dispersion, allowing the PTFE particles to be initially fixed on the substrate surface. Sintering is then performed in a muffle furnace with a slow heating rate of 5-10°C / min to prevent uneven heating, cracking, or detachment of the PTFE particles. A final temperature of 300-380°C, within the PTFE softening and melting range, promotes particle melting and fusion. Holding at this temperature for 20-40 minutes ensures sufficient coating, and the temperature is controlled below the PTFE decomposition temperature to maintain the integrity of the porous skeleton of the substrate. SEM images are shown below. Figure 2 As shown, polytetrafluoroethylene forms a continuous and uniform coating layer on the substrate surface, preserving the overall porous structure of the substrate. The contact angle test results are as follows: Figure 3 As shown, the material exhibits typical superhydrophobic properties. Because polytetrafluoroethylene molecules contain a large number of strongly hydrophobic fluorine atoms, its coating layer changes the chemical composition and micro-roughness of the substrate surface, forming an air cushion between the material surface and water molecules, which greatly reduces the contact area and thus prevents liquid water from penetrating into the substrate, maintains the gas phase environment of the pores, reduces the obstruction of liquid water to oxygen transport, and optimizes the mass transfer path of oxygen inside the electrode.

[0015] (3) Fix the polytetrafluoroethylene modified substrate onto a polytetrafluoroethylene plate, ensuring that one side of the polytetrafluoroethylene modified substrate is fully exposed and facing upwards. Perform surface corona etching in a corona machine, adjusting the corona machine voltage to 10,000-48,000 volts, with a distance of 5-10 mm between the substrate and the electrode. Perform corona etching treatment on the exposed surface of the polytetrafluoroethylene modified substrate for 80-140 seconds in an air atmosphere at room temperature.

[0016] It is understood that, in this embodiment of the application, by fixing the polytetrafluoroethylene (PTFE) modified substrate to a PTFE plate and fully exposing one side, the corona etching effect is concentrated on the target surface, avoiding interference from non-target areas. The corona generator operates at a high voltage of 10,000-48,000 volts, ionizing the gas in the room temperature air atmosphere to form high-energy corona plasma. The 5-10 mm gap between the substrate and the electrode provides suitable space for plasma generation and stable transmission, ensuring that active particles can effectively act on the substrate surface. During the etching process of 80-140 s, the high-energy plasma particles interact strongly with the surface of the PTFE modified layer, breaking the CF bonds in the long chain structure of PTFE, causing some fluorine atoms to detach from the molecular chain, exposing the surface of the carbon substrate coated with PTFE, and forming a large number of defects on the PTFE molecular chain. Both the exposed carbon substrate surface and the newly formed defect sites have high chemical activity. Fourier transform infrared spectroscopy shows that the intensity of the characteristic absorption peak of the CF bond decreases with increasing etching time. Figure 4 As shown, the process of breaking the CF bond is clearly demonstrated. The resulting active sites can significantly improve the adsorption and anchoring ability of the palladium catalyst on the substrate surface, laying the foundation for catalyst loading.

[0017] (4) After the corona treatment, place the electrode in an acidic electrolyte containing metal material and build a three-electrode system for deposition. Insert the three electrodes into the electrolytic cell and purge with nitrogen for 30 min. Set the electrochemical workstation to constant potential mode and deposit at the characteristic reduction overpotential of palladium -0.05V vs. Ag / AgCl. Control the electrolyte temperature at 25-30℃ and deposit for 10-30 min. After deposition, rinse the surface with deionized water to remove residual electrolyte 3-5 times. Apply 1% perfluorosulfonic acid resin solution to cover the catalyst layer. After drying, obtain the metal-loaded superhydrophobic air electrode.

[0018] It is understood that in this embodiment, a three-electrode system is constructed by using the corona-etched substrate as the working electrode and placing it in an acidic electrolyte containing a palladium precursor. The three-electrode system precisely controls the potential of the working electrode, providing a stable electrochemical environment for the directional deposition of palladium. Nitrogen gas is introduced into the electrolyte for 30 minutes. Utilizing the inertness and poor solubility of nitrogen, dissolved oxygen in the electrolyte is expelled, preventing oxygen from undergoing a reduction reaction on the surface of the working electrode during the deposition process, which would interfere with the reduction deposition of the palladium precursor. Subsequently, a constant potential mode is used for deposition at -0.05V vs. Ag / AgCl. This potential can precisely drive the palladium precursor in the electrolyte to undergo electron reduction. The original reaction involves the directional deposition of palladium nanoparticles onto the substrate surface. A deposition time of 10-30 minutes allows for control of the palladium particle loading and size, ensuring a uniformly distributed catalytic layer. After deposition, the electrode surface is repeatedly rinsed 3-5 times with deionized water to remove residual electrolyte and undeposited palladium precursors, preventing impurities from affecting subsequent catalytic performance. Finally, a 1% perfluorosulfonic acid resin solution is drop-coated. Perfluorosulfonic acid resin, as a proton-conducting polymer, not only fixes the palladium nanoparticles through its adhesive properties, preventing particle detachment, but also provides proton transport channels for the catalytic reaction. After drying, a stable catalytic layer is formed. Scanning electron microscopy (SEM) characterization is as follows. Figure 5 As shown, palladium nanoparticles are uniformly distributed on the surface of polytetrafluoroethylene-coated carbon fiber without damaging the original porous hydrophobic structure, ensuring that the electrode has both a good catalytic interface and a gas transport channel.

[0019] A third aspect of this application provides an application of a metal-supported superhydrophobic air electrode for the electrocatalytic production of active chlorine. The electrode is placed in a body of water containing chloride ions, and electrolysis is performed using cyclic voltammetry within a potential range of −0.3V to +0.3V relative to the Ag / AgCl electrode to generate active chlorine species.

[0020] Specifically, metal-loaded superhydrophobic air electrodes were used as both cathodes and anodes, placed together in water bodies to be treated with chloride ion concentrations of 50-500 mg / L and pH of 6-8. Electrolysis was performed using an electrochemical workstation with cyclic voltammetry at a scan rate of 50-100 mV / s and a scan potential range of -0.3 V to +0.3 V, versus an Ag / AgCl electrode. During the reaction, when the cathode voltage was applied to one electrode, the reduction current promoted the stepwise reduction of oxygen to generate hydrogen peroxide, which further generated hydroxyl radicals under the catalysis of the metal material. At the same time, on the other electrode under the anode voltage, chloride ions reacted with the in-situ generated hydroxyl radicals to generate active chloride species such as hypochlorite. Through the synergistic effect of the two electrodes, a chloride activation mechanism under a symmetrical electrode system was constructed.

[0021] The beneficial effects of this invention are as follows: 1. This invention uses IF8@zirconia as a porous substrate. The zirconia framework provides excellent chemical and mechanical stability, ensuring the long lifespan of the electrode under complex aquatic environments and electrochemical conditions. The ultra-high specific surface area and abundant unsaturated sites of the IF8 metal-organic framework can not only effectively enrich reactants, but may also have catalytic activity itself. It produces a synergistic catalytic effect with the supported noble metal nanoparticles, jointly improving the overall electrochemical activity and chlorine production efficiency. The superhydrophobic channels constructed by PTFE modification form a stable gas phase pathway inside the electrode, allowing oxygen to diffuse directly from the atmosphere to the reaction interface. Oxygen on the cathode side is reduced to H2O2 and further converted under the action of the metal catalyst. On the anode side, oxygen is self-supplied by the oxygen and dissolved oxygen it carries, and the electrode structure itself achieves oxygen self-supply, eliminating the need for traditional external aeration. 2. This invention precisely modifies the electrode surface through corona treatment, effectively breaking some carbon-fluorine bonds in the polytetrafluoroethylene layer to introduce a large number of metal catalyst anchoring sites, while perfectly maintaining the overall superhydrophobic properties and porous structure of the substrate. As a result, the successfully loaded metal catalyst is tightly coupled with the substrate, forming not only highly dispersed active sites, but also synergistically enhancing the electron transport capacity inside the electrode, laying the foundation for efficient and stable electrocatalytic reactions. 3. In the electrochemical chlorine production application of the present invention, the electrode system does not require external aeration equipment. The cathode directly utilizes oxygen from the atmosphere, while the anode utilizes dissolved oxygen in the water and oxygen carried by itself for the reaction. This feature fundamentally avoids the problems of high energy consumption and low bubble mass transfer efficiency of traditional aeration processes. 4. By setting the working potential window between -0.3V and +0.3V, this invention simultaneously suppresses the oxygen evolution reaction at the anode and the hydrogen evolution reaction at the cathode from the source. This design avoids the physical damage to the electrode structure caused by the oxygen evolution reaction and prevents the direct oxidation of organic matter by the anode to generate byproducts at high potentials. At the same time, it eliminates the hydrogen accumulation associated with the hydrogen evolution reaction and its potential explosion risk, significantly improving the operational safety of the system. 5. This invention achieves comprehensive advantages through a multi-stage synergistic design involving the selection of porous substrates, hydrophobic modification of polytetrafluoroethylene, corona etching to anchor the catalytic layer, and precise control of the working potential window. This results in optimized electrode mass transfer efficiency, guaranteed catalytic performance, reduced energy consumption costs, and improved operational safety. The combination of porous structure and superhydrophobic film solves the oxygen mass transfer resistance problem, while the coupling of corona treatment and metal catalyst enhances electron transport and catalytic activity. Together, they provide an efficient reaction environment for the electrochemical chlorine production reaction. Simultaneously, the elimination of external aeration equipment reduces energy consumption and process complexity, and the specific working potential window avoids side reactions and safety risks, significantly reducing the operating costs and operational hazards of the electrode system. Ultimately, the electrode maintains excellent electrochemical performance while possessing higher practical application adaptability, long-term operational stability, and economic efficiency, laying the foundation for the large-scale application of electrochemical chlorine production technology. Attached Figure Description

[0022] Figure 1 This is a scanning electron microscope (SEM) image of an IF8@zirconia porous substrate used in a method for fabricating a metal-loaded superhydrophobic air electrode according to an embodiment of this application. Figure 2 This is a scanning electron microscope image of a polytetrafluoroethylene-modified substrate electrode used in a method for preparing a metal-supported superhydrophobic air electrode according to an embodiment of this application. Figure 3 This is a hydrophobic angle diagram of a polytetrafluoroethylene-modified substrate electrode used in a method for preparing a metal-loaded superhydrophobic air electrode according to an embodiment of this application. Figure 4 Fourier transform infrared spectra of the electrode obtained by different corona etching treatments according to the method for preparing a metal-loaded superhydrophobic air electrode provided in the embodiments of this application. Figure 5 This is a scanning electron microscope image of the electrode after electrochemical in-situ deposition of a supported metal catalyst, according to a method for preparing a metal-supported superhydrophobic air electrode provided in an embodiment of this application. Figure 6 The image shows the electron paramagnetic resonance test results of a sample obtained by electrolysis experiment on the electrode of a metal-loaded superhydrophobic air electrode fabrication method according to an embodiment of this application. Figure 7 This is a standard quantitative curve for detecting the active chlorine concentration in a method for preparing a metal-supported superhydrophobic air electrode according to an embodiment of this application. Figure 8 The graph shows the quantitative analysis curve of active chlorine concentration in a sample obtained by electrolysis experiment of a metal-supported superhydrophobic air electrode preparation method according to an embodiment of this application. Detailed Implementation

[0023] To better understand the above technical solutions, exemplary embodiments of the present invention are described in more detail below. While exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the invention to those skilled in the art.

[0024] The following will describe, through specific embodiments, a method for preparing a metal-supported superhydrophobic air electrode and its application in chlorine production, including: Example 1

[0025] (1) Cut the substrate into 2cm×2cm sheet samples, place them in ethanol solution and deionized water in sequence, and ultrasonically treat them for 25min in an ultrasonic cleaner. After cleaning, dry them in a vacuum drying oven at 70℃ for 6h to obtain the pretreated substrate. (2) The pretreated substrate was completely immersed in a polytetrafluoroethylene dispersion with a solid content of 20% for 10 min, then removed and hung vertically for 1 min to drain. After drying, it was sintered in a muffle furnace with a heating rate of 10℃ / min, heated to 330℃, and held for 20 min to obtain the polytetrafluoroethylene modified substrate. (3) Fix the polytetrafluoroethylene modified substrate onto a polytetrafluoroethylene plate, ensuring that one side of the polytetrafluoroethylene modified substrate is fully exposed and facing upwards. Perform surface corona etching in a corona machine, adjust the corona machine voltage to 30,000 volts, and the distance between the substrate and the electrode is 10 mm. Perform corona etching treatment on the exposed surface of the polytetrafluoroethylene modified substrate for 90 s in a room temperature air atmosphere. (4) After the corona treatment, the electrode was placed in 20 mL of acetic acid-sodium acetate buffer electrolyte containing 5 mM potassium tetrachloropalladium. The electrolyte pH was 3.6. An electrochemical workstation three-electrode system was set up for deposition. The three electrodes were inserted into the electrolytic cell and nitrogen gas was introduced for 30 min. The electrochemical workstation was set to constant potential mode. Electrochemical deposition was carried out at -0.05 V (vs. Ag / AgCl) in constant potential mode. The deposition time was controlled at 20 min and the electrolyte temperature was controlled at 25℃. After deposition, the surface residual electrolyte was rinsed with deionized water 3 times. After drying, a metal-loaded superhydrophobic air electrode was obtained. Example 2

[0026] (1) Cut the substrate into 2cm×2cm sheet samples, place them in ethanol solution and deionized water in sequence, and ultrasonically treat them for 25min in an ultrasonic cleaner. After cleaning, dry them in a vacuum drying oven at 70℃ for 6h to obtain the pretreated substrate. (2) The pretreated substrate was completely immersed in a polytetrafluoroethylene dispersion with a solid content of 10% for 10 min, then removed and hung vertically for 1 min to drain. After drying, it was sintered in a muffle furnace with a heating rate of 10℃ / min, heated to 330℃, and held for 20 min to obtain the polytetrafluoroethylene modified substrate. (3) Fix the polytetrafluoroethylene modified substrate onto a polytetrafluoroethylene plate, ensuring that one side of the polytetrafluoroethylene modified substrate is fully exposed and facing upwards. Perform surface corona etching in a corona machine, adjust the corona machine voltage to 30,000 volts, and the distance between the substrate and the electrode is 10 mm. Perform corona etching treatment on the exposed surface of the polytetrafluoroethylene modified substrate for 90 s in a room temperature air atmosphere. (4) After the corona treatment, the electrode was placed in 20 mL of acetic acid-sodium acetate buffer electrolyte containing 5 mM potassium tetrachloropalladium. The electrolyte pH was 3.6. An electrochemical workstation three-electrode system was set up for deposition. The three electrodes were inserted into the electrolytic cell and nitrogen gas was introduced for 30 min. The electrochemical workstation was set to constant potential mode. Electrochemical deposition was carried out at -0.05 V (vs. Ag / AgCl) in constant potential mode. The deposition time was controlled at 20 min and the electrolyte temperature was controlled at 25℃. After deposition, the surface residual electrolyte was rinsed with deionized water 3 times. After drying, a metal-loaded superhydrophobic air electrode was obtained.

[0027] Compared with Example 1, Example 2 only changed the method of completely immersing the pretreated substrate in a polytetrafluoroethylene dispersion with a solid content of 20% to completely immersing it in a polytetrafluoroethylene dispersion with a solid content of 10%, while the other steps remained the same. Example 3

[0028] (1) Cut the substrate into 2cm×2cm sheet samples, place them in ethanol solution and deionized water in sequence, and ultrasonically treat them for 25min in an ultrasonic cleaner. After cleaning, dry them in a vacuum drying oven at 70℃ for 6h to obtain the pretreated substrate. (2) The pretreated substrate was completely immersed in a polytetrafluoroethylene dispersion with a solid content of 20% for 10 min, then removed and hung vertically for 1 min to drain. After drying, it was sintered in a muffle furnace with a heating rate of 10℃ / min, heated to 330℃, and held for 20 min to obtain the polytetrafluoroethylene modified substrate. (3) Fix the polytetrafluoroethylene modified substrate onto a polytetrafluoroethylene plate, ensuring that one side of the polytetrafluoroethylene modified substrate is fully exposed and facing upwards. Perform surface corona etching in a corona machine, adjust the corona machine voltage to 30,000 volts, and the distance between the substrate and the electrode is 10 mm. Perform corona etching treatment on the exposed surface of the polytetrafluoroethylene modified substrate for 90 s in a room temperature air atmosphere. (4) After the corona treatment, the electrode was placed in 20 mL of acetic acid-sodium acetate buffer electrolyte containing 5 mM potassium tetrachloropalladium. The electrolyte pH was 3.6. An electrochemical workstation three-electrode system was set up for deposition. The three electrodes were inserted into the electrolytic cell and nitrogen gas was introduced for 30 min. The electrochemical workstation was set to constant potential mode. Electrochemical deposition was carried out at -0.05 V (vs. Ag / AgCl) in constant potential mode. The deposition time was controlled at 10 min and the electrolyte temperature was controlled at 25℃. After deposition, the surface residual electrolyte was rinsed with deionized water 3 times. After drying, a metal-loaded superhydrophobic air electrode was obtained.

[0029] Compared with Example 1, Example 3 only changed the electrodeposition time of palladium from 20 min to 10 min, while the other steps remained the same.

[0030] Comparative Example 1 (1) Cut the substrate into 2cm×2cm sheet samples, place them in ethanol solution and deionized water in sequence, and ultrasonically treat them for 25min in an ultrasonic cleaner. After cleaning, dry them in a vacuum drying oven at 70℃ for 6h to obtain the pretreated substrate. (2) The pretreated substrate was completely immersed in a polytetrafluoroethylene dispersion with a solid content of 20% for 10 min, then removed and hung vertically for 1 min to drain. After drying, it was sintered in a muffle furnace with a heating rate of 10℃ / min, heated to 330℃, and held for 20 min to obtain the polytetrafluoroethylene modified substrate.

[0031] Compared with Example 1, Comparative Example 1 omits the corona treatment and metal nanomaterial deposition steps, and uses a substrate modified only by polytetrafluoroethylene as the substrate electrode.

[0032] Comparative Example 2 (1) Cut the substrate into 2cm×2cm sheet samples, place them in ethanol solution and deionized water in sequence, and ultrasonically treat them for 25min in an ultrasonic cleaner. After cleaning, dry them in a vacuum drying oven at 70℃ for 6h to obtain the pretreated substrate. (2) Fix the polytetrafluoroethylene modified substrate onto a polytetrafluoroethylene plate, ensuring that one side of the polytetrafluoroethylene modified substrate is fully exposed and facing upwards. Perform surface corona etching in a corona machine, adjust the corona machine voltage to 30,000 volts, and the distance between the substrate and the electrode is 10 mm. Perform corona etching treatment on the exposed surface of the polytetrafluoroethylene modified substrate for 90 s in a room temperature air atmosphere. (3) After the corona treatment, the electrode was placed in 20 mL of acetic acid-sodium acetate buffer electrolyte containing 5 mM potassium tetrachloropalladium. The electrolyte pH was 3.6. An electrochemical workstation three-electrode system was set up for deposition. The three electrodes were inserted into the electrolytic cell and nitrogen gas was introduced for 30 min. The electrochemical workstation was set to constant potential mode. Electrochemical deposition was carried out at -0.05 V (vs. Ag / AgCl) in constant potential mode. The deposition time was controlled at 20 min and the electrolyte temperature was controlled at 25℃. After deposition, the surface residual electrolyte was rinsed with deionized water 3 times. After drying, a metal-loaded superhydrophobic air electrode was obtained.

[0033] Compared with Example 1, Comparative Example 2 omits the hydrophobic modification step of polytetrafluoroethylene and directly deposits palladium nanomaterials on the substrate without hydrophobic modification.

[0034] Comparative Example 3 (1) Cut the substrate into 2cm×2cm sheet samples, place them in ethanol solution and deionized water in sequence, and ultrasonically treat them for 25min in an ultrasonic cleaner. After cleaning, dry them in a vacuum drying oven at 70℃ for 6h to obtain the pretreated substrate. (2) The pretreated substrate was completely immersed in a polytetrafluoroethylene dispersion with a solid content of 20% for 10 min, then removed and hung vertically for 1 min to drain. After drying, it was sintered in a muffle furnace with a heating rate of 10℃ / min, heated to 330℃, and held for 20 min to obtain the polytetrafluoroethylene modified substrate. (3) The polytetrafluoroethylene modified substrate electrode was placed in 20 mL of acetic acid-sodium acetate buffer electrolyte containing 5 mM potassium tetrachloropalladium. The electrolyte pH was 3.6. An electrochemical workstation three-electrode system was set up for deposition. The three electrodes were inserted into the electrolytic cell and nitrogen gas was introduced for 30 min. The electrochemical workstation was set to constant potential mode. Electrochemical deposition was carried out at -0.05 V (vs. Ag / AgCl) in constant potential mode. The deposition time was controlled at 20 min and the electrolyte temperature was controlled at 25℃. After deposition, the surface residual electrolyte was rinsed with deionized water 3 times. After drying, a metal-loaded superhydrophobic air electrode was obtained.

[0035] Compared with Example 1, Comparative Example 3 omits the corona etching step and directly deposits palladium nanomaterials on the polytetrafluoroethylene modified substrate.

[0036] Test case Electron paramagnetic resonance (EPR) was used to detect hydroxyl radicals. In the electrochemical system, the prepared palladium-based superhydrophobic air electrode was used as the working electrode and placed in an electrolyte solution containing 50 mM sodium sulfate. Cyclic voltammetry was performed using an electrochemical workstation at a scan rate of 50 mV / s within a potential window relative to Ag / AgCl, from -0.3 V to +0.3 V. After the reaction had proceeded for a certain time, 1 mL of the reaction solution was quickly taken from the electrode interface region and immediately mixed with an equal volume of freshly prepared 100 mM 5,5-dimethyl-1-pyrrolline-N-oxide aqueous solution in a 2.5 mL centrifuge tube. The mixture was vortexed for 5-10 s to ensure complete reaction. Subsequently, the mixture was rapidly transferred into a quartz capillary EPR sample tube and placed in the resonant cavity of the EPR spectrometer 2 min after sampling. Scanning was performed at room temperature. The EPR test results are shown below. Figure 6 As shown, a quadruple characteristic peak with an intensity ratio of 1:2:2:1 appears in the spectrum. This signal is consistent with the characteristics of the adduct formed after hydroxyl radicals are captured by DMPO, indicating that under the experimental conditions, the catalytic oxygen reduction process on the electrode surface generates hydroxyl radicals via a chain reaction pathway.

[0037] Active chlorine detection The palladium-based superhydrophobic air electrodes prepared in Examples 1-3 and Comparative Examples 1-3 were used as working electrodes, graphite electrodes as counter electrodes, and silver / silver chloride as reference electrodes, respectively, to conduct electrolytic chlorine production experiments to investigate the amount of active chlorine accumulated by different electrodes. The volume of the reaction solution was 60 ml, the size of both the working electrode and the counter electrode was 2 cm × 2 cm, the electrode spacing was 2 cm, cyclic voltammetry was used, the scan rate was 50 mV / s, and the applied potential was +0.3 V to -0.3 V.

[0038] The results of active chlorine production accumulated in the electrodes prepared in Examples 1-3 and Comparative Examples 1-3 are as follows: Figure 8 The quantitative standard curve of active chlorine is as follows: Figure 7Example 1, using optimal parameters—20% PTFE hydrophobic treatment, corona etching, and a 20-minute deposition time—exhibited the highest active chlorine yield, with an active chlorine concentration reaching 2 ppm after 20 minutes of electrolysis. In Example 2, with PTFE concentration reduced to 10%, the increase in active chlorine concentration was slightly slower within the same timeframe. This was because insufficient hydrophobicity in the PTFE concentration led to electrolyte intrusion, hindering oxygen mass transfer. In Example 3, with metal electrodeposition shortened to 10 minutes, performance declined due to a reduction in catalytic active sites. Comparative Example 1 omitted corona treatment and metal nanomaterial deposition. In Example 1, only a polytetrafluoroethylene (PTFE) modified substrate electrode was obtained. It had excellent oxygen mass transfer channels but lacked effective catalytic centers, resulting in extremely low chlorine production capacity. In Comparative Example 2, the PTFE hydrophobic modification step was omitted, and palladium nanomaterials were directly deposited on the unmodified substrate. Because a stable gas-liquid-solid reaction interface could not be established, effective oxygen mass transfer could not be achieved, and the amount of active chlorine generated was the lowest. In Comparative Example 3, the corona etching step was omitted, and palladium nanomaterials were directly deposited on the PTFE modified substrate. Compared with Example 1, the yield of active chlorine decreased slightly, indicating that corona etching increased the anchoring sites of the catalyst, making the catalytic reaction more efficient.

[0039] The above results indicate that a high-performance chlorine-producing electrode requires a suitable hydrophobicity to provide a high-quality oxygen mass transfer channel, metal loading to provide a catalytic center, and corona etching to increase catalyst anchoring sites. This suggests that the synergistic effect of its hydrophobic structure, surface modification, and highly loaded catalyst can significantly promote oxygen reduction and chlorine activation efficiency.

[0040] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A metal-loaded superhydrophobic air electrode, characterized in that, The metal-loaded superhydrophobic air electrode includes: Porous substrate; A polytetrafluoroethylene (PTFE) modified layer is formed on the porous substrate by an impregnation sintering method, which makes the substrate superhydrophobic. A metal catalyst layer is grown directly on the surface of the polytetrafluoroethylene modified layer.

2. The metal-loaded superhydrophobic air electrode according to claim 1, characterized in that, The porous substrate is an IF8@zirconia porous substrate.

3. The metal-loaded superhydrophobic air electrode according to claim 2, characterized in that, The preparation method of the IF8@zirconia porous substrate includes: S1. Porous zirconia with a three-dimensional interconnected network structure was prepared by combining foam template method with sintering process; S2. Zirconium salt, organic ligand and regulator are dissolved in an organic solvent and reacted by a solvothermal method to prepare IF8 crystal dispersion; S3. The porous zirconia support is immersed in the IF8 crystal dispersion, and the IF8 crystals are grown in situ in the channels and surface of the porous zirconia by vacuum-assisted impregnation and secondary solvothermal method to form an IF8@zirconia composite structure. S4. The loaded composite material is taken out, cleaned with an organic solvent, dried, and then annealed and activated under an inert atmosphere to obtain the IF8@zirconia porous substrate.

4. The metal-loaded superhydrophobic air electrode according to claim 1, characterized in that, The metal catalyst is selected from any one of platinum, palladium, gold, iridium, and ruthenium, or is an alloy or composite nanomaterial composed of a noble metal and one or more non-noble metals selected from iron, cobalt, nickel, copper, and manganese.

5. A method for preparing a metal-supported superhydrophobic air electrode as described in any one of claims 2-4, characterized in that, The preparation method includes the following steps: (1) The IF8@zirconia porous substrate pre-cut to a specific size was placed in ethanol solution and deionized water in sequence, and ultrasonically treated for 25 min in an ultrasonic cleaner. After cleaning, it was dried in a vacuum drying oven at 70℃ for 6 h, and then cooled to 25℃ to obtain the pre-treated substrate. (2) The pretreated substrate is completely immersed in a polytetrafluoroethylene dispersion with a solid content of 10%-30% for 5-10 min, then taken out and hung vertically for 1-3 min to drain. After drying, it is sintered in a muffle furnace with a heating rate of 5-10℃ / min, heated to 300-380℃, and held for 20-40 min to obtain a polytetrafluoroethylene modified substrate. (3) Fix the polytetrafluoroethylene modified substrate onto a polytetrafluoroethylene plate, ensuring that one side of the polytetrafluoroethylene modified substrate is fully exposed and facing upwards. Perform surface corona etching in a corona machine, adjusting the corona machine voltage to 10000-48000 volts, with a distance of 5-10 mm between the substrate and the electrode. Perform corona etching treatment on the exposed surface of the polytetrafluoroethylene modified substrate for 30-150 seconds in an air atmosphere at room temperature. (4) After the corona treatment, place the electrode in an acidic electrolyte containing metal material and build a three-electrode system for deposition. Insert the three electrodes into the electrolytic cell and purge with nitrogen for 30 minutes. Set the electrochemical workstation to constant potential mode and deposit the electrode at the specific reduction potential of the metal material. Control the electrolyte temperature at 25-30℃ and deposit for 10-30 minutes. After deposition, rinse the surface with deionized water to remove residual electrolyte 3-5 times. Apply 1% perfluorosulfonic acid resin solution to cover the catalyst layer. After drying, obtain the metal-loaded superhydrophobic air electrode.

6. The method for preparing a metal-supported superhydrophobic air electrode according to claim 5, characterized in that, In step (4), the three-electrode system of the electrochemical workstation consists of a working electrode, a reference electrode, and a counter electrode. The working electrode is a polytetrafluoroethylene modified substrate after corona treatment, with an exposed area of ​​2cm×2cm. The reference electrode is a silver or silver chloride electrode, and the counter electrode is a graphite electrode with an exposed area of ​​2cm×2cm.

7. The method for preparing a metal-supported superhydrophobic air electrode according to claim 5, characterized in that, In the acidic electrolyte of the metal material in step (4), the metal precursor is compatible with the acidic electrolyte. The metal precursor is selected from any one of palladium chloride, palladium chloride, chloroplatinic acid, iridium chloride, ruthenium trichloride, silver nitrate, copper sulfate, cobalt chloride, nickel nitrate, and ferric chloride. The acidic electrolyte is an aqueous solution of inorganic acid or organic acid. The inorganic acid is selected from any one of hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid. The organic acid is selected from any one of formic acid, acetic acid, and oxalic acid.

8. The application of a metal-supported superhydrophobic air electrode as described in any one of claims 1-4 in electrochemical chlorine production, characterized in that, The electrode was placed in a body of water containing chloride ions, and electrolysis was performed using cyclic voltammetry within a potential range of −0.3V to +0.3V relative to the Ag / AgCl electrode to generate active chloride species.

Citation Information

Patent Citations

  • Preparation method of air diffusion electrode for preparing methanol by electrochemically reducing carbon dioxide

    CN101931081A

  • Gas diffusion electrode, preparation method thereof and fuel cell

    CN114361474A

  • Platinum-titanium electrode with three-dimensional aerophilic structure, preparation method and application of platinum-titanium electrode and device for preparing hypochlorous acid through electro-catalysis ORR pairing

    CN116752184A

  • Gas diffusion electrode suitable for use in carbon dioxide electrolyzer and membrane electrode assembly including said gas diffusion electrode

    US20230407495A1

  • Electrolysis device for chlorine production

    US9273405B1

Cited By

  • Gas diffusion electrode based on polytetrafluoroethylene membrane, low-temperature and large-area preparation method and application

    CN121496422A

  • Boron etching modified gas diffusion electrode preparation method and in-situ hydrogen peroxide production application

    CN122235753A